External Validation and Evaluation of Adding MRI or Extended Myositis Antibody Panel to the 2017 EULAR/ACR Myositis Classification Criteria. Issue 7 (8th August 2019) - Luu, Queenie; Day, Jessica; Hall, Alix; Limaye, Vidya; Major, Gabor
Abstract : Objective: To externally validate the European League Against Rheumatism/American College of Rheumatism (EULAR/ACR) classification criteria for idiopathic inflammatory myositis (IIM) and determine the optimal cut points for Australian patients. To determine the level of agreement with traditional criteria and assess the effect of including magnetic resonance imaging (MRI) and an extended myositis antibody panel as well as extending histological criteria to include myofiber invasion. Methods: Data were collected on adult patients referred for muscle biopsy to two Australian teaching hospitals. Patients were scored for "risk of IIM" according to EULAR/ACR criteria, using clinician diagnosis as the gold standard. Results: Overall, 87 of 204 patients had IIM. For patients with muscle biopsy, the optimal cut point of 5.25 (sensitivity 90%, specificity 89%) was lower than the EULAR/ACR cut point of 6.7, which in our cohort showed reduced sensitivity (71% vs 93%) but comparable specificity (89% vs 88%). We found moderate agreement between the EULAR/ACR criteria and Bohan and Peter (κ = 0.45, 95% confidence interval [CI] = 0.28, 0.62, P < 0.001) and Targoff (κ = 0.40, 95% CI = 0.23, 0.57, P < 0.001). Inclusion of MRI (area under curve [AUC] = 0.86, 95% CI = 0.79, 0.93) or non‐Jo1 antibodies (AUC = 0.84, 95% CI = 0.77, 0.91) as covariates improved the probability of IIM diagnosis (AUC = 0.80, 95% CI = 0.75, 0.86). Extending histologic criteria to include myofiber invasion slightly improved sensitivity (75% vs 71%) with the same level of specificity (89% vs 89%). Conclusion: Application of the EULAR/ACR criteria to an Australian cohort showed comparable specificity but lower sensitivity, and a lower optimal cut point. Inclusion of MRI or non‐Jo1 antibodies as covariates may improve the accuracy of determining the probability of IIM diagnoses. Extending the histologic criteria to include myofiber invasion did not reduce specificity.